MEASURING THE USER EXPERIENCE OF INTERACTIVE E-MODULES BASED ON SOMATIC, AUDITORY, VISUAL, INTELLECTUAL ON LIGHT MATERIAL - Muhammad Rizqi Alvian; Enny Susiyawati (EDUPROXIMA : Jurnal Ilmiah Pendidikan IPA, 2024)
This study aims to evaluate the use of interactive e-modules based on Somatic, Auditory, Visual, Intellectual (SAVI) in the learning process with light material. Several multimedia aspects are presented in this interactive e-module (such as video, sound, picture, etc.). To collect relevant information, this descriptive research involved 27 students grade 8 from a State Islamic Junior High School in Kediri. A valid and reliable User Experience Questionnaire (UEQ) was use to examine students’ experience while using SAVI-based interactive e-module. The SAVI-based interactive e-modules received good responses for each user experience questionnaire indicator. The good response from the students showed that the SAVI-based interactive e-modules was good to use in learning process.